Intelligent Soft Surgical Robots for Next‐Generation Minimally Invasive Surgery. (5th May 2021) - Zhu, Jiaqi; Lyu, Liangxiong; Xu, Yi; Liang, Huageng; Zhang, Xiaoping; Ding, Han; Wu, Zhigang
Abstract : Endowed with the expected visions for future surgery, minimally invasive surgery (MIS) has become one of the most rapid developing areas in modern surgery. Soft robotics, which originates from interdisciplinary advances in materials, fabrication, and electronics, featuring better adaptability and safer interaction, holds great promises in addressing current technical challenges in MIS, which are difficult to be solved with current rigid robotic technologies. For the first time, herein, the expected characteristics of next‐generation MIS from the surgeons' perspectives are analyzed and the recent progress of soft surgical instruments from three different aspects is comprehensively summarized: engineering design, fabrication techniques, and human–robot interaction. Perspectives of next‐generation soft surgical robots are then discussed, where some exciting possibilities are emphasized. It is believed that further developments of intelligent soft robotics enable the next‐generation MIS to agilely navigate to the target and conduct dexterous diagnostic or therapeutic procedures without any trade‐offs in invasiveness and ultimately be a propitious solution for future surgery. Abstract : Recent progress of soft surgical robots for minimally invasive surgery (MIS) is comprehensively summarized and discussed based on the analyzed expected characteristics from the surgeons' perspectives. Soft materials and new design concepts is the hope to redefine/expand current surgical robots and bring some exciting possibilities for the next‐generation MIS.